Hydrogen absorption–desorption characteristics of a Gd2Co7-type Sm1.6Mg0.4Ni7 compound. Issue 24 (31st May 2016) - Zhang, Lu; Ding, Yanqiao; Li, Yuan; Zhao, Yumeng; Zhao, Xin; Liu, Baozhong; Han, Shumin
Abstract : The Gd2 Co7 -type Sm1.6 Mg0.4 Ni7 compound can absorb 1.88 wt% H2 and retain 99.3% the initial hydrogen content after 100 cycles. Abstract : In this paper, we report a new Gd2 Co7 -type Sm1.6 Mg0.4 Ni7 compound as a hydrogen storage material with a special hydrogen absorption/desorption process and good hydrogen storage ability. The Gd2 Co7 -type Sm1.6 Mg0.4 Ni7 compound absorbs 1.88 wt% H2 within 17 min at 298 K under 10 MPa H2 . Meanwhile, the hydrogen absorption speed accelerates to 3.4 min after 20 hydrogenation/dehydrogenation cycles with a 1.44 wt% H2 under 3 MPa H2 . Especially, the capacity retention of the compound is 99.3% at the 100 th cycle. We found the hydrogen absorption/desorption of the compound undergoes two equilibrium stages, relating to the transformation of H2 between H-solid solution phase and hydride phase with a lower rate and higher enthalpy change at the lower concentration H2 stage, and the direct conversion between H2 and the hydride phase with a higher rate and lower enthalpy change at the higher concentration H2 stage. The two step mode lowers the inner-molecular strain and mismatch in subunit volumes of the compound in hydrogen absorption/desorption, caused by the transformation of H2 at the lower concentration of H2 stage, thus leading to good structural stability and excellent cycling stability. The new insights are expected to provide viable intermetallic materials as high-pressure tank materials for hydrogen storage with nice hydrogen storage properties.